2021
DOI: 10.1371/journal.pone.0254138
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome of Geomydoecus aurei, a pocket-gopher louse

Abstract: Parasitic lice demonstrate an unusual array of mitochondrial genome architectures and gene arrangements. We characterized the mitochondrial genome of Geomydoecus aurei, a chewing louse (Phthiraptera: Trichodectidae) found on pocket gophers (Rodentia: Geomyidae) using reads from both Illumina and Oxford Nanopore sequencing coupled with PCR, cloning, and Sanger sequencing to verify structure and arrangement for each chromosome. The genome consisted of 12 circular mitochondrial chromosomes ranging in size from 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The evidence available to date indicates that mt genome fragmentation occurred independently at least 14 times among parasitic lice (infraorder Phthiraptera): once in eutherian mammal lice in three parvorders (Anoplura, Rhynchophthirina, and Trichodectera) [16,20], four to five times in amblyceran lice ( [20], and the present study), and nine times in ischnoceran lice [20]. The independent evolution of fragmented mt genomes is also supported by the observations of the typical single-chromosome mt genomes in 16 amblyceran species from four different families (Boopiidae, Laemobothriidae, Menoponidae, and Ricinidae) ( [16,17,22,23], and the current study), in 10 ischnoceran species from 10 genera [16,18,21,41], but not in any species in Anoplura, Rhynchophthirina, or Trichodectera [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Mitochondrial Genome Fragmentation Occurred Multiple Times I...supporting
confidence: 86%
See 2 more Smart Citations
“…The evidence available to date indicates that mt genome fragmentation occurred independently at least 14 times among parasitic lice (infraorder Phthiraptera): once in eutherian mammal lice in three parvorders (Anoplura, Rhynchophthirina, and Trichodectera) [16,20], four to five times in amblyceran lice ( [20], and the present study), and nine times in ischnoceran lice [20]. The independent evolution of fragmented mt genomes is also supported by the observations of the typical single-chromosome mt genomes in 16 amblyceran species from four different families (Boopiidae, Laemobothriidae, Menoponidae, and Ricinidae) ( [16,17,22,23], and the current study), in 10 ischnoceran species from 10 genera [16,18,21,41], but not in any species in Anoplura, Rhynchophthirina, or Trichodectera [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Mitochondrial Genome Fragmentation Occurred Multiple Times I...supporting
confidence: 86%
“…Valuable Information for Resolving Phylogenetic Relationships at Different Taxonomic Levels Song et al [16] showed that mt genome fragmentation and minichromosomal characters united parasitic lice of eutherian mammals in three parvorders: Anoplura, Rhyn-chophthirina, and Trichodectera. All species in these three parvorders studied to date have fragmented mt genomes with a varying number of minichromosomes, from 9 to 20 in each species [4][5][6][7][8][9][10][11][12][13][14][15]17]. When only protein-coding and rRNA genes (these genes are more stable than tRNA genes in chromosomal locations) are considered, five minichromosomes, which contain cox1, nad4, nad5, rrnS, and rrnL, respectively, are in common among all eutherian mammal lice in these three parvorders, whereas other minichromosomes are variable [16].…”
Section: Minichromosomal Characters Derived From Mitochondrial Genome...mentioning
confidence: 99%
See 1 more Smart Citation